Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I recently got stuck on evaluating the following integral. I do not know an effective substitution to use. Could you please help me evaluate:

$$\int_{0}^{\infty} \ln\left(1 - e^{-x}\right) \,\mathrm dx $$

share|cite|improve this question
Use braces for longer exponents, so e^{-x}, not e^-x – t.b. Aug 29 '11 at 7:54
I've edited the LaTeX so that $e^{-x}$ appears correctly (and also merged your accounts, Jack). – Zev Chonoles Aug 29 '11 at 7:55
The integrand is undefined, since $e^{-x}-1$ is negative. Do you mean $\ln|e^{-x}-1|$? – Hans Lundmark Aug 29 '11 at 7:55
Yes, I dropped a negative sign from in front of the integrand and have edited the question. – Jack Rousseau Aug 29 '11 at 9:12
up vote 46 down vote accepted

One route to evaluating the integral is $$-\int_0^\infty \ln(1-e^{-x})dx=\int_0^\infty\left(e^{-x}+\frac{e^{-2x}}{2}+\frac{e^{-3x}}{3}+\cdots\right)dx $$ $$=\int_0^\infty e^{-x}dx+\frac{1}{2}\int_0^\infty e^{-2x}dx+\frac{1}{3}\int_0^\infty e^{-3x}dx+\cdots$$ $$=1+\frac{1}{2}\cdot\frac{1}{2}+\frac{1}{3}\cdot\frac{1}{3}+\frac{1}{4}\cdot\frac{1}{4}\cdots $$ $$=\zeta(2)=\frac{\pi^2}{6}.$$

I don't know if a straightforward substitution could get you the answer, what with this being the Riemann zeta function and all, but you can see the integrals on the linked page and try your own hand at finding one. (Or someone else can try their hand.)

share|cite|improve this answer
Thank you, this is what I was looking for! Another post observed that zeta(2) is the area under the curve e^-x + e^-y = 1 and now I guess I have more to think about. haha – Jack Rousseau Aug 29 '11 at 9:22
@Jack: Was it…, by any chance? – Hans Lundmark Aug 29 '11 at 11:29
Yes it was. - I see now, that my question was answered in that thread. @Hans: I find your comment there very intriguing. – Jack Rousseau Aug 29 '11 at 20:44

Integrating by parts it is easily reducible to integral representation of $\Gamma(s) \zeta(s)$ at $s=2$:

$$\begin{eqnarray*} \int_0^\infty \log\left(1-\mathrm{e}^{-x}\right) \, \mathrm{d} x &=& \lim x \log\left(1-\mathrm{e}^{-x}\right) \vert_{0^+}^\infty - \int_0^\infty x \frac{\mathrm{e}^{-x}}{1 - \mathrm{e}^{-x}} \mathrm{d} x \\ &=& - \int_0^\infty x \frac{\mathrm{e}^{-x}}{1 - \mathrm{e}^{-x}} \mathrm{d} x = -\Gamma(2) \zeta(2). \end{eqnarray*} $$

share|cite|improve this answer

Not as snazzy as anon's answer, but:

If you start with the usual series for the logarithm:

$$-\frac{\log(1-x)}{x}=\sum_{k=0}^\infty \frac{x^k}{k+1}$$

the dilogarithm function $\mathrm{Li}_2(x)$ is

$$\mathrm{Li}_2(x)=-\int_0^x\frac{\log(1-t)}{t}\mathrm dt=\sum_{k=1}^\infty \frac{x^k}{k^2}$$

From the series representation, we find that $\mathrm{Li}_2(1)=\dfrac{\pi^2}{6}$; it remains to manipulate the integral

$$-\int_0^1\frac{\log(1-t)}{t}\mathrm dt=\int_1^0\frac{\log(1-t)}{t}\mathrm dt$$

Letting $t=\exp(-u),\quad \mathrm dt=-\exp(-u)\mathrm du$, we get

$$-\int_0^\infty\frac{\log(1-\exp(-u))}{\exp(-u)}\exp(-u)\mathrm du$$

which is the negative of the OP's integral.

share|cite|improve this answer

A related family of integrals is the following. Consider the polylogarithm function, $\mathsf{Li}_{s}(x) = \sum_{k \geq 1} \frac{x^{k}}{k^{s}}$. By Parseval's Theorem, $$ \int_{0}^{1} | \mathsf{Li}_{s}(e^{2 \pi i x})|^{2} dx = \sum_{k \geq 1} \left| \frac{e^{2 \pi i k x}}{k^{s}} \right|^{2} = \sum_{k \geq 1} \frac{1}{k^{2s}} = \zeta(2s). $$ Since $\mathsf{Li}_{1}(x) = - \ln (1 - x)$, we have $$ \int_{0}^{1} | \ln (1 - e^{2\pi i x})|^{2} dx = \zeta(2). $$

share|cite|improve this answer

Consider following parametric integral$$I(\alpha )=\int_{0}^{\infty} \ln\left(1 - \alpha e^{-x}\right) \,\mathrm dx$$

We have $I(0)=0$ and $I(1)$ will yield required integral

$$I'(\alpha )=-\int_{0}^{\infty} \frac{e^{-x}}{1-\alpha e^{-x}} \,\mathrm dx= \left[\frac{x}{\alpha }-\frac{\ln \left(e^x-\alpha \right)}{\alpha }\right]_0^{\infty}=\frac{\ln(1-\alpha )}{\alpha }$$

$$I(\alpha )=-\operatorname{Li}_2(\alpha )+c$$

$$I(0)=0\implies I(\alpha )=-\operatorname{Li}_2(\alpha )$$


$$\large\int_{0}^{\infty} \ln\left(1 - e^{-x}\right) \,\mathrm dx=-\frac{\pi^2}{6}$$

share|cite|improve this answer

Maybe this answer is too late. Let $t=1-e^{-x}$. Then $$ \int_0^\infty\ln(1-e^{-x})dx=\int_0^1\frac{\ln t}{1-t}dt=-\frac{\pi^2}{6}. $$

share|cite|improve this answer
+1 For nice answer! – Iuʇǝƃɹɐʇoɹ Dec 10 '14 at 10:55
@Integrator, your answer is nice too. Actually, both our answers are the same. – xpaul Dec 10 '14 at 13:51

break $\ln(1-e^{-x})$ like $\ln(1-t) = y-y^2/2-y^3/3- \cdots$ where $y = e^{-x}$ then break at the addition/subtraction point in integration. then evaluate.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.